PREGNANCY AND HERITABLE CONNECTIVE TISSUE DISORDERS (MARFAN SYNDROME, EHLERS DANLOS SYNDROME, OSLER-WEBER-RENDU DISEASE) - L. S. Radetskaya (Акушерство, гинекология и репродукция, 2016)
The article describes some inherited disorders (Marfan syndrome, Ehlers-Danlos syndrome, Osler-Weber-Rendu disease) that affects the connective tissue with prominent manifestations in the skeletal, ocular, and cardiovascular systems during the pregnancy. The present article aims to provide an overview of these rare but very important hereditary disorders. Diagnosing of these disorders can be difficult because the symptoms can vary significantly from person to person. There are clinical criteria and molecular methods of diagnostics. The pathogenesis of these inherited connective tissue disorders has not been fully elucidated. Pregnancy can be dangerous in such patients due to the high risk of lifetreating complications. Cesarean section is preferred in women with inherited connective tissue disorders.